Characterization of Bistre Pigment Samples by FTIR, SERS, Py-GC/MS and XRF. Issue 1656 (22nd August 2014) - Roldan, María L.; Centeno, Silvia A.; Rizzo, Adriana; van Dyke, Yana
ABSTRACT: A combination of FTIR, normal Raman, SERS, Py-GC/MS and XRF was used to analyze commercial bistre samples to determine specific biomarkers that will allow for a rapid identification of the pigment in works of art. The results of the XRF analysis showed that potassium, calcium and iron are the main elements present. Characteristic bands belonging to phenolic components of lignin were observed in the FTIR spectra. The SERS analysis provided a fingerprint that may originate in the polymerization of the phenolic components catalyzed by the presence of the nanostructured silver surface under alkaline conditions. The Py-GC/MS analysis revealed the presence of lignin and cellulose biomarkers and a series of polycyclic aromatic hydrocarbons. The similarities observed between the commercial samples studied suggest that both originate in the same raw material, hardwood. The results demonstrate the potential of the multi-technique approach used for the characterization of this complex black-brown pigment.